Identifying Effective Solutions for Improving the Informative Effectiveness of Hotels’ Websites (Case Study: Top Hotels of Touristic Cities in Iran) - Saeed Jafari Moghadam; Nooshin Hashemi (Journal of Information Technology Management)
Poorinformative websites of hotels in Iranian tourist destinations has turned to a deterrent factor in attracting potential tourists from all over the world. The main goal of this study was to identify effective solutions for improving the informative effectiveness of Iranian top hotels’ websites based on interviews with 25 hotel managers (i.e. CEOs, Public Relations Managers and IT Managers). Interviewees were selected through purposive sampling from the research population (including, three, four and five star hotels of Tehran and Isfahan-the most touristic cities in Iran). Designing an initial conceptual framework for research based on literature review and analysis of the collected information from interviews, by means of open coding technique resulted in identifying four effective dimensions on informative effectiveness of hotels’ websites. Basically on the basis of their roles these dimensions were ranked as follows: customer orientation, technology orientation, marketing orientation and tendency towards security. Research results could improve informative effectiveness of hotels’ websites as well as number of domestic and especially foreign tourists through changing attitude of hotel managers and encouraging professional associations state authorities in the related field.